Large scale metrology - Scarr, A. J. (College of Aeronautics, 1964)
INTRODUCTION It has been recognised in industry that the measurement of large components to high orders of accuracy presents a particularly difficult problem. This fact has been emphasised by a survey carried out by the N.P.L. (Ref. 1) in which a number of engineering firms in Great Britain were asked to declare the size of several prepared test pieces ranging in diameter from 15 inches to 80 inches. In general terms the result of this investigation showed that, under industrial conditions using conventional equipment, it was not possible V declare the size of large components to an accuracy of better than - 30 parts in a million under workshop conditions and - 15 parts in a million under inspection conditions. The survey also showed that above 20 inches the accuracy of determination of internal diameters was somewhat higher than for external diameters. The purpose of this paper is to indicate the main problems associated with measuring large sizes and to describe the experimental work undertaken at the College of Aeronautics in the design and testing of a new type of stick micrometer for internal diameters and micrometer frame for external diameters.